2014
DOI: 10.1007/978-981-4585-27-9_17
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilities of Smart Grid State Estimation Against False Data Injection Attack

Abstract: In recent years, Information Security has become a notable issue in the energy sector. After the invention of 'The Stuxnet worm' [1] in 2010, data integrity, privacy and confidentiality has received significant importance in the real-time operation of the control centres. New methods and frameworks are being developed to protect the National Critical Infrastructures like-energy sector. In the recent literatures, it has been shown that the key real-time operational tools (e.g., State Estimator) of any Energy Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The existence of outlier values may be rigorously impaired the estimation results and needs an adequate caution to be taken. This fact has been studied by many researchers in view of point estimation for the unknown state parameters (Anwar and Mahmood 2014). To this reason end, the performance of the proposed interval estimation had also been carried out in the presence of contaminated measurements.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…The existence of outlier values may be rigorously impaired the estimation results and needs an adequate caution to be taken. This fact has been studied by many researchers in view of point estimation for the unknown state parameters (Anwar and Mahmood 2014). To this reason end, the performance of the proposed interval estimation had also been carried out in the presence of contaminated measurements.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Equations (6) and (7) express the current and voltage magnitude at bus n, respectively, in complex form as:…”
Section: Optimal Power Flowmentioning
confidence: 99%
“…Traditional state estimators are capable of identifying and eliminating bad data from state estimations [13] [14]. However, it has been recently found that malicious data attacks can exploit system topology information to construct false data injection schemes that will bypass bad data detectors in conventional state estimation [15][16] [17]. A number of defending strategies have been proposed [18], [19], [20].…”
Section: Background and Related Workmentioning
confidence: 99%